por favor me Ajudem e pra amanhã.
Anexos:
![](https://pt-static.z-dn.net/files/d5c/5c850c126c531c0e8fa5c7798c72b959.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
y=√3x/3+4√3-7
Explicação passo-a-passo:
K(-12, -7) => xo= -12 e yo= -7
m=tg30°=√3/3
y-yo=m(x-xo)
y-(-7)=√3/3[x-(-12)]
y+7=√3/3(x+12)
y=√3x/3+(√3/3).12-7
y=√3x/3+4√3-7
stefanisilva27:
vlw
Perguntas interessantes
Inglês,
10 meses atrás
Matemática,
10 meses atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás